Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2002
DOI: 10.1145/503376.503448
|View full text |Cite
|
Sign up to set email alerts
|

Unremarkable computing

Abstract: In this paper, we seek to contribute to the Ubiquitous Computing agenda by focusing on one of its earliest, but most difficult, design ambitions -making technology "invisible in use". We draw on field studies of domestic life as this domain is becoming increasingly important for new technologies and challenges many of the assumptions we take for granted in the design of technologies for the workplace. We use some examples of domestic routines to identify a number of insights into what it means for features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(56 citation statements)
references
References 12 publications
0
56
0
Order By: Relevance
“…This is discussed by several previous authors, e.g. [6,7,18]. Harper et al [6] calls this workflow control or workflow management.…”
Section: Awarenessmentioning
confidence: 94%
See 1 more Smart Citation
“…This is discussed by several previous authors, e.g. [6,7,18]. Harper et al [6] calls this workflow control or workflow management.…”
Section: Awarenessmentioning
confidence: 94%
“…Part of this is derived from familiarity, where people know the routines of other household members-what they do when they come home, where they go, where they leave things like keys or purses-and use this knowledge in deciding where to leave messages. As Tolmie et al [18] found "Routines are resources for action, and knowledge of others' routines can be resources for interaction. "…”
Section: Pathways and Routinesmentioning
confidence: 99%
“…As they envisioned, when interactions with technology would be available to be undertaken both in the user's periphery and center of attention, people could be in control of technology without being overburdened by it. Similar to interactions with our everyday environment, calm technology is intended to support technology in becoming a seamless or unremarkable [1] part of everyday routines.…”
Section: Related Research and Designmentioning
confidence: 99%
“…These technologies are often equipped with user interfaces such as keyboards and touch screens: traditional methods of human-computer interaction (HCI) that typically require focused attention during interaction. As a result of these developments, researchers in the field of HCI have foreseen a challenge in fluently embedding computing technologies in people's everyday routines [1][2][3]. To address this challenge, Weiser and Brown envisioned calm technology [3], an approach inspired by the observation that many interactions with the physical world take place in the background or periphery of attention, while they may also engage the center of attention when this is relevant or desired.…”
Section: Introductionmentioning
confidence: 99%
“…Areas such as ubiquitous computing, augmented reality, and physical computing have made it evident that the personal computer is just one out of many possible ways in which we can design how humans interact with computers [12]. The design of these devices should be carefully done so that they consider the contextual qualities of the environment such as aesthetics, emotions and aspirations whether they are place indoor in home, museums or outdoor in public places [15] [36] [34]. For example, when designing an ambient display, one should notice an ambient display because of a change in the data it is presenting and not because its design clashes with its environment [35].…”
Section: Evaluation Of Artifactsmentioning
confidence: 99%